Charles Babbage (1791-1871) e a mecanização do cálculo: das engrenagens à máquina de pensar - Costa, Eli Banks Liberato da (2012)
The theme of the origins of computers has aroused controversies that are not always well enlightened. This paper intends to contribute to the subject focusing on the mechanical calculating machines designed in the first half of the nineteenth century by Charles Babbage (1791-1871). It presents the main motivations of its inventor, his ideas, difficulties and ingenuity to face some completely new and challenging technical problems. We also analyze the French motivations and solution to solve calculus problems. In the context of that time, we examined carefully the question of communication between man and machine, so far an intriguing innovation that generated enthusiasm, controversy and many speculations. We highlight Babbage s perception that there was "some slight analogy to the operation of the faculty of memory", an idea shared by some of his contemporaries. Even at that time, then, the idea of the "thinking machine" arose, ancestor of the more recent idea of the "electronic brain". Finally we refer to the not so expressive Babbage s technical legacy as opposed to a meaningful and engaging fact that he stimulated an opening for a new and fascinating human activity: the dialogue between man and the machine of his creation. Keywords